1988
DOI: 10.1002/1097-0142(19880201)61:3<462::aid-cncr2820610310>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin sensitive suppressor-cell activity in head and neck cancer patients: The role of the adherent mononuclear cell

Abstract: Head and neck cancer (H&N CA) patients have known depression of cell-mediated immunity. There is suggestive evidence that prostaglandin (PCE+secreting cells may be a major factor. The authors have sought to determine the role of PGEZ-releasing monocytes-macrophages in this immune depression by determining the effects of adherent cell depletion and by measuring the effects of indomethacin, a PGEl synthetase inhibitor, on selected tests of lymphocyte function. Lymphocyte stimulation with phytohem-agglutinin (PHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…While studies have clearly shown that patients with HSNCC have profound immune dysfunction, very few studies have examined the immunological environment in premalignant oral lesions [46]. In addition, most studies with patients have focused on immune mediators, especially inhibitory mediators, in the peripheral blood rather than in the oral tissues [4,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have clearly shown that patients with HSNCC have profound immune dysfunction, very few studies have examined the immunological environment in premalignant oral lesions [46]. In addition, most studies with patients have focused on immune mediators, especially inhibitory mediators, in the peripheral blood rather than in the oral tissues [4,26].…”
Section: Discussionmentioning
confidence: 99%
“…Among the hallmarks of HNSCC is the profound inhibition of immune competence that is mediated in part by immunosuppressive cell populations including immune inhibitory macrophages, T-cells that are skewed toward a Th2 phenotype, Treg cells, myeloid-derived suppressor cells (MDSC) and the less mature CD34 + progenitor cells [46]. While systemic immune suppression is prominent in patients with HNSCC, immune alterations during the premalignant stage have not been well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of immune suppressor cells induced by other cancer types have focused on the peripheral blood, not on the intratumoral infiltrate (Gooding et al, 1995;Wanebo et al, 1993). Among the immune suppressor cells that have been identified in patients with HNSCC as well as other cancers are suppressive monocytes (Wanebo et al, 1988). Suppressor T-cell have been described in the peripheral blood of patients with breast and ovarian cancers (Yacyshyn et al, 1995) but there remains little support for their contribution to the immune suppressed state of patients with HNSCC cancers (Letessier et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Some human cancers induce suppressive T-cells that are inhibitory to immune functions, including anti-tumor T-cell reactivities (Chakraborty et al, 1991). Suppression of T-cell function in patients with HNSCC as well as with other cancers can also be due to monocytes or macrophages secreting the immune suppressive mediator prostaglandin E 2 (Wanebo et al, 1988). In one study with a small number of patients, HNSCC patients were treated with low-dose cyclophosphamide to reduce suppressor T-cells and with indomethacin to block the inhibitory activity of macrophages (Hadden et al, 1994).…”
mentioning
confidence: 99%
“…Based on these data and on the well-known impaired cytotoxicity and cytokine-production in peripheral blood mononuclear cells from head and neck cancer (Walter et al, 1985;Beauchamp et al, 1988;Wanebo et al, 1988), we investigated IL-l beta and IL-6 spontaneous and (LPS)-stimulated production by freshly isolated blood monocytes from patients with advanced head and neck squamous cancer (HNSC) in comparison to healthy subjects.…”
mentioning
confidence: 99%